2015
DOI: 10.4102/koedoe.v57i1.1248
|View full text |Cite
|
Sign up to set email alerts
|

Artisanal Fisheries in the Ndumo Area of the Lower Phongolo River Floodplain, South Africa

Abstract: The aim of this study was to investigate the status of artisanal fisheries in the lower Phongolo River floodplain in northern KwaZulu-Natal, South Africa. A cross-sectional quantitative survey design was used that included the development of a questionnaire and a systematic survey among the five villages bordering the Ndumo Game Reserve. Data were collected over a 5-day period by a group of 16 fieldworkers and analysed using the Statistical Package for the Social Sciences, version 21. The results revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…The function of zooplankton and macroinvertebrates as a food source in the food web structure (Medeiros & Arthington 2008) is crucial to higher trophic feeders especially birds that are unique to this floodplain (Whittington et al 2013) and fish that are a source of protein to the local communities (Coetzee et al 2015). Therefore, effective fisheries management and biodiversity conservation in the Phongolo floodplain should account for fish-invertebrate and resource-invertebrate linkages.…”
Section: Management and Conservation Implicationsmentioning
confidence: 99%
“…The function of zooplankton and macroinvertebrates as a food source in the food web structure (Medeiros & Arthington 2008) is crucial to higher trophic feeders especially birds that are unique to this floodplain (Whittington et al 2013) and fish that are a source of protein to the local communities (Coetzee et al 2015). Therefore, effective fisheries management and biodiversity conservation in the Phongolo floodplain should account for fish-invertebrate and resource-invertebrate linkages.…”
Section: Management and Conservation Implicationsmentioning
confidence: 99%
“…Although P. clarkii has been introduced to several African countries and caused visible impacts (Lowery & Mendes, 1977; Mikkola, 1996; Foster & Harper, 2006), in South Africa the species is only known from a single locality and does not seem to be spreading (Nunes et al, 2017). Populations of C. quadricarinatus are more widespread in the country (Du Preez & Smit, 2013; Van Rooyen, 2013; Coetzee et al, 2015; De Villiers, 2015) and have also been reported from Swaziland (De Moor, 2002), Zimbabwe (Marufu, Phiri & Nhiwatiwa, 2014), Zambia and Mozambique (Chivambo, Nerantzoulis & Mussagy, 2013; Nunes et al, 2016). Globally, C. quadricarinatus has been translocated to non-native areas in Australia (Doupé et al, 2004; Leland, Coughran & Furse, 2012) and Indonesian territories (Patoka et al, 2016), and wild populations are also known from Israel (Snovsky & Galil, 2011), Jamaica (Todd, 2005; Pienkowski et al, 2015), Mexico (Bortolini, Alvarez & Rodriguez-Almaraz, 2007; Vega-Villasante et al, 2015; Torres-Montoya et al, 2016), Puerto Rico (Williams et al, 2001), Singapore (Ahyong & Yeo, 2007; Belle et al, 2011) and Slovenia (Jaklič & Vrezec, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed started harvesting it (Coetzee et al, 2015), increasing the risk of translocations for commercial reasons. The possible introduction of this species into new catchments in Africa is a matter of extreme concern, especially given the high speed at which the species has been expanding and its potential impacts on native biota, such as disease introductions, competitive interactions with native freshwater crustaceans or habitat modifications (de Moor, 2002;Nunes et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Populations of C. quadricarinatus are more widespread in the country (du Preez & Smit, 2013;van Rooyen, 2013;Coetzee et al, 2015;de Villiers, 2015) and have also been reported from Swaziland (de Moor, 2002), Zimbabwe (Marufu, Phiri & Nhiwatiwa, 2014), Zambia and Mozambique (Chivambo, Nerantzoulis & Mussagy, 2013;Nunes et al, 2016). Globally, C. quadricarinatus has been translocated to non-native areas in Australia (Doupé et al, 2004;Leland, Coughran & Furse, 2012) and Indonesian territories (Patoka et al, 2016), and wild populations are also known from Israel (Snovsky & Galil, 2011), Jamaica (Todd, 2005;Pienkowski et al, 2015), Mexico (Bortolini, Alvarez & Rodriguez-Almaraz, 2007;Vega-Villasante et al, 2015;Torres-Montoya et al, 2016), Puerto Rico (Williams et al, 2001), Singapore (Ahyong & Yeo, 2007;Belle et al, 2011) and Slovenia (Jaklič & Vrezec, 2011).…”
Section: Introductionmentioning
confidence: 99%